135 ASSOCIATION OF TRICUSPID REGURGITATION WITH OUTCOME IN ACUTE HEART FAILURE. (15th December 2022) - Cocianni, Daniele; Stolfo, Davide; Perotto, Maria; Contessi, Stefano; Barbisan, Davide; Savonitto, Giulio; Rizzi, Jacopo Giulio; Barbati, Giulia; Merlo, Marco; Altinier, Alessandro; Sinagra, Gianfranco
Abstract: Background: Tricuspid regurgitation (TR) is common in chronic heart failure (HF) and is associated with negative prognosis. However, evidence on prognostic implications of TR in acute HF (AHF) is lacking. Objectives: We sought to investigate the association between TR and mortality and the interaction with pulmonary hypertension (PH) in patients admitted for AHF. Methods: We enrolled 1176 consecutive patients with a primary diagnosis of AHF and with available non-invasive estimation of TR and pulmonary arterial systolic pressure (PASP). Results: Moderate-severe TR was present in 352 patients (29.9%) and was associated with older age and more comorbidities. The prevalence of PH (i.e., PASP>40mmHg), right ventricular dysfunction (RVD) and mitral regurgitation (MR) was higher in moderate-severe TR. At 1 year, 184 (15.6%) patients died. Moderate-severe TR was associated with higher 1-year mortality risk after adjustment for other echocardiographic parameters (PASP, left ventricle ejection fraction – LVEF, RVD and MR; HR=1.623, p=0.004) and the association with outcome was maintained when clinical variables were added to the multivariable model (HR=1.515, p=0.035). The association between moderate-severe TR and outcome was consistent in patients with vs without PH, with vs without RVD, and with vs without LVEF<50%. Patients with coexistent moderate-severe TR and PH had 3-fold higher 1-year mortality risk compared to patients with no TR or PH (HR=2.920, p<0.001). Conclusions: In patients hospitalized for AHF, the severity of TR is associated with 1-year survival, regardless of the presence of PH. However, the combination of moderate-severe TR and PH conferred a further incremental mortality risk.